Hand hygiene habit and pathogens found in medical students - Domínguez Navarrete, Nicanor (2021)
The objective was to know the hand hygiene habits of medical students; as well as the bacterial population resident in the palm of the hands. An observational, descriptive cross-sectional study was carried out. Likewise, a hand hygiene behavior survey was carried out on 100 students, and a microbiological culture of the palmar surface was carried out on 33 other students. Regarding hygiene habits, 74% showed an appropriate attitude. The hygiene attitude was appropriate in 41.3% and 46% in relation to the prevention of contagion. The following pathogenic microorganisms were isolated: S.aureus with 20 cases (60.6%), P. aeruginosa, Enterobacter and S.viridans, one in each case. Therefore, workshops or dissemination campaigns should be organized to raise awareness and modulate hand hygiene habits in students.